A Literary (Techno)science: The Silent Speech of Erkki Kurenniemi’s 2048 Performance - Hollingshaus, Wade (Nordic Theatre Studies, 2019)
Beginning in the late 1970s, Finland’s Erkki Kurenniemi (1941-2017) actively labored to archive every possible aspect of his life. He took photos, made videos, and collected his tram tickets, receipts, body hairs, etc. Kurenniemi believed that within the next forty years, computer technoscience will have advanced sufficiently that it could be programmed to interpret the data of his archive and—on his 107th birthday, 10 July 2018—resurrect his consciousness. For Kurenniemi, this project was an experiment in the realms of neuroscience and artificial intelligence. However, it can also be seen as an experiment in aesthetics, or in what Jacques Rancière calls the “aesthetic regime” of art—an aesthetic-political historical framework imbued with the dynamics of democracy, where “everything speaks.” This article reframes Kurenniemi’s work within the aesthetic regime of art to draw attention to the “silent speech” and “aesthetic unconscious” (Rancière) of the work and what is the literary nature of Kurenniemi’s experiments with (techno)science.